Analysis of Social Intelligence of Sellers by MESI Methodology - Lucia ZBIHLEJOVA (Communications of International Proceedings, 2022)
Social intelligence can be considered an important competence in the work of sellers and at the same time an important predictor of sales success. This paper focuses on the analysis of individual attributes of social intelligence as perceived by sellers. The research was carried out using the MESI methodology designed to measure the following attributes of social intelligence: Manipulation, Empathy and Social Irritability. The research sample used to perform the factor analysis included participation of 95 retailers of consumer goods. The results support the consistency in the factor structure of the MESI methodology as assessed by sellers.
Keywords: social intelligence; sellers; MESI methodology; factor analysis